Outpost in the desert [large type] - Vaughan, Robert, 1937-2024 (Center Point Large Print, 2025)
"Lawless lands, frontier strife, and an epic battle of heart over legacy. John Mason never imagined his path to a comfortable life in Washington, D.C., would detour through the unforgiving terrain of Fort Verde, deep in Apache territory. A young second lieutenant, he hoped to serve his time quietly, but the violent tension brewing between the Army and the Apache nation has upended that possibility. Old Kohana and his braves seek peace, while ruthless warrior Talako vows to expel the white man from his people's sacred lands. With Fort Verde's drunken commander firmly under control, the fate of both the Apaches and John's future hangs in the balance. If he intervenes to prevent the impending massacre, he risks court-martial and imprisonment. But if he remains silent, he will lose Sakari Blue Stream. Raised by an Apache chief after being saved as a child, Sakari is torn between her love for John and her loyalty to her people. John's heart is also divided, haunted by the shadow of his father's heroic legacy and the difficult choice between duty and disgrace. The choices John makes will determine not only his future but the fate of the land itself. And in a place where loyalty is tested and love stands on a knife's edge, he must decide who he truly is before it's too late."--